Mastering Options : Effective and Profitable Strategies for Traders. - Cooper, Philip (Business Expert Press, 2018)
If you are a beginner to the world of options, this will be essential to learn the basics of option strategies that will enable you to start making consistently handsome earnings. This book gives the novice a comprehensive understanding of using option investment and hedging strategies successfully. It is primarily aimed at the undergraduate whose ambition is to either become a trader in a financial organization or an online investor through a financial broker's trading platform. It also provides seasoned investors and traders with new insights into using options as an investment tool. In simple-to-understand, concise language, enhanced by relevant graphics, the key trading tools available on online trading platforms are explained in enough detail that beginners will be able to understand as well as learn how to invest effectively in the financial markets using options. Chapter by chapter, this book builds a complete understanding of the basic building blocks of investing in options, including covering key charting techniques using technical tools.